Clinical and radiological analysis of the causes for endodontic treatment failure - Nešković Jelena; Jovanović Medojević Milica; Živković Slavoljub (Serbian Medical Society - Dental Section, Belgrade, 2017)
Introduction Development of inflammatory lesions or their persistence after primary treatment is considered endodontic failure. The reason for failure can be complex anatomy of the canal system and numerous iatrogenic factors. The objective of this study was to analyze, clinically and radiographically, the causes of primary endodontic treatment failure and assess possibilities for retreatment of teeth with failed endodontic treatment. Method The study included 79 teeth (36 multirooted and 43 singlerooted tooth) indicated for repeated endodontic treatment. Based on the radiographic assessment of the status of periapical structures, teeth were divided into two groups. The first group included teeth without periapical lesions, i.e. the healthy periodontal tissues (PAI score of 1 and 2) in which retreatment was required for prosthodontic reason due to the poor quality of obturation (28 teeth), and the second group included teeth with visible signs of periapical tissue damage (PAI scores 3, 4 and 5) (51 teeth). In both groups, quality of obturation, coronal sealing and the presence or absence of clinical symptoms was analyzed. Results The most common radiographic finding of definitive obturation was short filling (65.8% of cases); "forgotten" canals (25.3%); non-homogeneous obturation with correct length (5.1%) and fractured instrument (3.8%). There was significant difference between healthy periodontal ligament and adequate restoration (P < 0.001). In 95% of patients with symptoms, changes in the periapical tissue were observed. Also, there was significant difference in the presence of symptoms after primary treatments, between the teeth with healthy apical periodontal tissue and teeth with periapical lesions (P = 0.019). Conclusion The outcome of the root canal treatment is significantly affected by the quality (density) of obturation and the presence and quality of coronal restoration. In patients with symptoms there were changes in the periapical tissue.